2017
DOI: 10.3389/fcimb.2017.00295
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Targeting by Fusobacterium nucleatum: A Pilot Study and Future Perspectives

Abstract: Colorectal adenocarcinoma (CRC) is a common tumor with high mortality rates. Interestingly, CRC was found to be colonized by the oral anaerobic bacteria Fusobacterium nucleatum, which accelerates tumor progression and enables immune evasion. The CRC-specific colonization by fusobacteria is mediated through the recognition of tumor displayed Gal-GalNAc moieties by the fusobacterial Fap2 Gal-GalNAc lectin. Here, we show high Gal-GalNAc levels in additional adenocarcinomas including those found in the stomach, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 34 publications
(57 reference statements)
5
51
0
Order By: Relevance
“…A few studies have investigated the underlying pathomechanisms for the apparent prevalence of Fusobacteria in cancers. The spread of oral Fusobacteria to the colorectal cancer is thought to be enabled by a transient bacteremia, such as those seen in Fusobacterium infections [16]. The All the above studies, including our study, suggest that Fusobacteria play an important part in the human microbiome of the gut, and the pathomechanisms regarding colorectal cancer evolution and growth.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…A few studies have investigated the underlying pathomechanisms for the apparent prevalence of Fusobacteria in cancers. The spread of oral Fusobacteria to the colorectal cancer is thought to be enabled by a transient bacteremia, such as those seen in Fusobacterium infections [16]. The All the above studies, including our study, suggest that Fusobacteria play an important part in the human microbiome of the gut, and the pathomechanisms regarding colorectal cancer evolution and growth.…”
Section: Discussionsupporting
confidence: 60%
“…These data suggest a link, also in lung cancer, between the bacterial constitution and the cancer. To support this, a recent study compiled data, that suggest that through the Gal-GalNAc, Fusobacteria may be linked to many different cancers, including breast, lung and esophagus cancers [16]. Further studies in lung cancer are required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). Interestingly, these taxa are commonly found in patients with CRC 57 , with the Fusobacterium genus frequently being associated with tumor progression 58 . Moreover, CpT samples possessed microbial genera commonly involved in development of intestinal disease or pathologies, such as Streptococcus (taxonomic trend prevalence of 80.00% in CpT) and Gemella (taxonomic trend prevalence of 80% in CpT) 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Our metagenomic analysis revealed that CpT samples had a higher abundance of the Fusobacteria phylum compared to healthy samples. Interestingly, the Fusobacterium genus is often involved in tumor progression 58 , 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study suggest that colorectal carcinogenesis may be significantly suppressed by sustained intake of food such as probiotics or prebiotics. In contrast, Fusobacterium nucleatum has attracted attention as the cause of colorectal cancer (21)(22)(23). For example, FadA Adhesin, a fungal component of the nucleatum, degrades E-cadherin on the cell membrane and binds to β-catenin via p120 to activate oncogenic signalling via pathways such as Wnt/β-catenin (24).…”
Section: Discussionmentioning
confidence: 99%